2020
DOI: 10.1111/cote.12461
|View full text |Cite
|
Sign up to set email alerts
|

The effect of liposome on dyeing mohair/wool blends

Abstract: The aim of this study was to examine the use of liposome in the dyeing of wool and mohair fibres with acid dyestuffs. Soybean lecithin and cholesterol were used to form the liposome membrane utilised in the dyebath. Liposome production was performed according to the thin lipid layer method (Bangham Method) using a rotary evaporator. Two different forms of liposome were used for dyeing wool and mohair fibres. In its first form, liposome was utilised as an auxiliary agent, where it was added to a conventional dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Alkali solubility varies depending on the type of woollen product, its structure, the processes applied and the use to which it will be exposed 25,28 . According to studies in the literature, it has been observed that the alkali solubility values of wool are between 10% and 13% and that they change according to the type of treatment 25,28–30 . The alkali solubility results for the first group of bio‐bleached wool samples are provided in Figure 11 and those for the second group in Figure 12.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkali solubility varies depending on the type of woollen product, its structure, the processes applied and the use to which it will be exposed 25,28 . According to studies in the literature, it has been observed that the alkali solubility values of wool are between 10% and 13% and that they change according to the type of treatment 25,28–30 . The alkali solubility results for the first group of bio‐bleached wool samples are provided in Figure 11 and those for the second group in Figure 12.…”
Section: Resultsmentioning
confidence: 99%
“…25,28 According to studies in the literature, it has been observed that the alkali solubility values of wool are between 10% and 13% and that they change according to the type of treatment. 25,[28][29][30] The alkali solubility results for the first group of biobleached wool samples are provided in Figure 11 and those for the second group in Figure 12. When examining the alkaline results for both groups, it was noted that enzymatic treatment gave higher results in all samples than nonenzymatic treatment.…”
Section: Alkali Solubilitymentioning
confidence: 99%
“…Lipozomal taşıma sistemi (LDS) olarak adlandırılmakta olan bu sistemler son on yılda dikkate değer ilerleme göstermiştir [15]. Enkapsülasyon veya lipozom teknolojisi; kapsüllenmiş materyalin yavaş yavaş serbest bırakılmasının önemli olduğu eczacılık, kozmetik, deterjan, tekstil ve bunun gibi çok çeşitli alanlarda uygulanabilmektedir [16][17][18][19][20][21][22]. Ayrıca; gıda ve beslenme endüstrisinde, lipozomlar enzim, vitamin ve antioksidanların stabilitesini artırmak için de kullanılmaktadırlar [15].…”
Section: Introductionunclassified
“…The exploitation of natural auxiliaries in wool dyeing is interesting as a topic because it has the potential to save energy by reducing both the processing time and temperature used. Gökhan Erkan and colleagues from Dokuz Eylül University, Turkey, study the application of liposomes in the dyeing of wool/mohair fibres with acid dyes . In their paper, liposomes are prepared with soybean lecithin and cholesterol according to the thin lipid layer method.…”
mentioning
confidence: 99%